UN GENERAL DE NAPOLEÓN EN ESPAÑA: CONVENCIÓN Y TRANSPOSICIÓN LITERARIA DE 1808 - Dubroca, Danielle; Flores, Ángela; Hernández Álvarez, Mª Vicenta (Anales de Filología Francesa, 2008)
General Thiébault wrote his Memoirs in the 1830s. His memories of his time in Spain and the Peninsular War have suffered from the passing of time and literary transposition. Thiébault reorganized his past and his place in history: stereotypes representing the conquered country and its people run through his writing.